Regeneration of osteochondral defects in vivo by a cell‐free cylindrical poly(lactide‐co‐glycolide) scaffold with a radially oriented microstructure - Dai, Yuankun (2020)
A scaffold with an oriented porous architecture to facilitate cell infiltration and bioactive interflow between neo‐host tissues is of great importance for in situ inductive osteochondral regeneration. In this study, a poly(lactide‐co‐glycolide) (PLGA) scaffold with oriented pores in its radial direction was fabricated via unidirectional cooling of the PLGA solution in the radial direction, following with lyophilization. Micro‐computed tomography evaluation and scanning electron microscopy observation confirmed the radially oriented microtubular pores in the scaffold. The scaffold had porosity larger than 90% and a compressive modulus of 4 MPa in a dry state. Culture of bone marrow stem cells in vitro revealed faster migration and regular distribution of cells in the poly(lactide‐co‐glycolide) scaffold with oriented pores compared with the random PLGA scaffold. The cell‐free oriented macroporous PLGA scaffold was implanted into rabbit articular osteochondral defect in vivo for 12 weeks to evaluate its inductive tissue regeneration function. Histological analysis confirmed obvious tide mark formation and abundant chondrocytes distributed regularly with obvious lacunae in the cartilage layer. Safranin O‐fast green staining showed an obvious boundary between the two layers with distinct staining results, indicating the simultaneous regeneration of the cartilage and subchondral bone layers, which is not the case for the random poly(lactide‐co‐glycolide) scaffold after the same implantation in vivo. The oriented macroporous PLGA scaffold is a promising material for the in situ inductive osteochondral regeneration without the necessity of preseeding cells.